2013
DOI: 10.1007/s00520-013-1799-2
|View full text |Cite
|
Sign up to set email alerts
|

The use of fentanyl buccal tablets for breakthrough pain by using doses proportional to opioid basal regimen in a home care setting

Abstract: The dose of rapid onset opioids to be given for breakthrough cancer pain (BTcP) is controversial. Dose proportional to the basal opioid regimen seem to be safe and effective in hospital units. However, data in other less protected settings, like home care, are lacking. The aim of this open-label study was to assess the efficacy and safety in a group of patients with BTcP followed at home, after giving a dose of fentanyl buccal tablets (FBT) proportional to the opioid basal regimen, skipping the steps for dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
2
12
0
3
Order By: Relevance
“…24 No preference for 1 of the 2 products was given by patients who received both delivery systems. The other important finding is that both treatments in doses proportional to the basal opioid dose used for background pain were effective as well as tolerable, confirming experience accumulated through the years and the findings of some controlled studies, [13][14][15][16][17][18][19][20][21][22][23][24] even when higher doses were used. Finally, despite a similar analgesic trend, FPNS had a major impact at the intervals taken into consideration.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…24 No preference for 1 of the 2 products was given by patients who received both delivery systems. The other important finding is that both treatments in doses proportional to the basal opioid dose used for background pain were effective as well as tolerable, confirming experience accumulated through the years and the findings of some controlled studies, [13][14][15][16][17][18][19][20][21][22][23][24] even when higher doses were used. Finally, despite a similar analgesic trend, FPNS had a major impact at the intervals taken into consideration.…”
Section: Discussionsupporting
confidence: 61%
“…For instance, the only existing controlled study performed using a fentanyl buccal tablet has evidenced that proportional doses are more effective than the dose titration approach, without higher risks of adverse effects, 22 confirming a series of open-label studies in which proportional doses were highly effective and well tolerated. [13][14][15][16][17][18][19][20][21][22][23][24][25] Finally, there is clinical legend suggesting that the rescue dose of opioids for BTP should be 10% of the daily dose of scheduled opioids. Several studies of proportional doses have shown that to produce meaningful and clinical analgesic effects, it is necessary to administer 15 to 20% of the daily dose.…”
Section: Discussionmentioning
confidence: 99%
“…On 15th March 2010, the Italian government approved a new law (n. 38), with the intent to improve pain assessment and treatment, imposing physicians and nurses to register the characteristics of pain in any patient's chart. According to these new indications from the Minister of Health, a group of experts started a program to organize a national observatory for exploring these activities.…”
Section: Introductionmentioning
confidence: 99%
“…In a"real world" study reproducing a clinical scenario of patients receiving opioids for BTP, while the dose of oral opioids used as rescue medication was 18% of the around the clock opioid dose, for oral transmucosal fentanyl titrated to determine the effective dose, the rescue dose was about 35% of the around the clock dose [16], suggesting that titration process may provide even higher doses than those expected by using proportional doses to the basal regimen. For instance, the only existing controlled study, performed with fentanl buccal tablet, has evidenced that proportional doses are more effective than the dose titration approach, without higher risks of adverse effects [17], confirming a series of open-label studies performed by my group in which proportional doses were highly effective and well tolerated [18,19], even at home [20]. Large epidemiological studies of characterization of BTP by using a predefinite algorithm and comparison studies of ROOs, used in proportional doses, are ongoing.…”
Section: Breakthrough Painmentioning
confidence: 62%